Pumped Storage Hydropower as a Part of Energy Storage Systems in Poland—Młoty Case Study - Jarosław Kulpa; Michał Kopacz; Kinga Stecuła; Piotr Olczak (Energies, 2024)
The increase in the share of renewable energy sources (RES) leads to a growing need for sources or systems/actions to stabilize the national energy grid. Such stabilizing actions include market tools, such as prices and demand-side response (DSR) tools, as well as flexible energy sources (e.g., gas). In addition, energy storage, where pumped storage hydroelectricity (PSH) accounts for 90% of global storage capacity, plays an important role. Therefore, the authors presented a detailed analysis of PSH in the context of the dynamic growth of installed capacity in renewable energy sources. They analyzed the economic viability of this type of power plant, with a particular emphasis on operational costs, energy production, and revenue. The Młoty case study and market data, including historical data on various PSH, were presented and analyzed. This study uses copulas, simulation, and statistical analysis. The authors proved that market prices and arbitrage actions alone are not sufficient to achieve profitability of the investment; however, additional benefits, such as fees for available power, enable the achievement of economic profitability. The reason for this is the fact that one of the main goals of PSH is to serve as a power reserve. In addition, this paper presents the analysis of the utilization of existing PSH in the form of full pumping and energy generation cycles (charging and discharging storage).